A Review of Energy Harvesting Methods for Power Transmission Line Monitoring Sensors - Yeesparan, Suganthi; Baharuddin, Mohd Zafri Bin; Md Din, Norashidah Bt; Haron, Mohamad Halil (International Journal of Engineering and Technology, 2018)
Condition monitoring sensors have the responsibility of reducing occupational failures or unscheduled shutdowns especially in power transmission line systems. Existing sensors that are used for condition monitoring are mostly battery-dependent. Powering up these sensors in difficult to access areas where high voltage transmission line usually runs is a challenge because batteries usually have a limited life cycle. Power sources other than batteries such as harvesting from solar energy, magnetic energy, radio frequency energy either produces insufficient energy or not entirely available all the time. Electric Field Energy Harvesting (EFEH) overcomes many of these disadvantages and provides a quality and continuous power source to be used to power up devices especially the monitoring sensors that are used in transmission line monitoring. This paper presents key aspects and drawbacks of six types of energy harvesting methods and a review of existing energy harvesters. The concept of electric field and the usage of EFEH in power transmission line system are explained and a comparison between EFEH with typical energy harvesting methods is discussed. This paper finds that EFEH devices have potential to provide sufficient energy for low powered condition monitoring sensors. Moreover, several improved EFEH approaches are proposed, and future trends are discussed.